2023
DOI: 10.3390/su15064829
|View full text |Cite
|
Sign up to set email alerts
|

Probability-Based City-Scale Risk Assessment of Passengers Trapped in Elevators under Earthquakes

Abstract: An accurate prediction of the number of passengers trapped in elevators under earthquakes in urban areas is essential for promoting earthquake emergencies. A probability-based city-scale method for assessing the earthquake-induced risk of passenger entrapment in elevators was proposed, in which city-scale time history analysis was performed to simulate the seismic response of building clusters, and the Monte Carlo simulation was conducted to consider the uncertainty of multiple factors, including the mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…In the comparative study, various sets of representative buildings (i.e., Sets 1, 2, and 3 in Table 2) were selected, and the PTE numbers under the MCE-level earthquake were correspondingly quantified. It can be found that the mean standard deviation of three sets reaches 12.8 when the method proposed in Gu et al (2023) is adopted while that decreases to 4.0 when the population heatmap is utilized to quantify the popularities of buildings in this study, demonstrating that Gu et al (2023) is significantly sensitive to the selection of representative buildings while the population heatmap-powered method in this study is robust. In Gu et al (2023), it was assumed that buildings with the same occupancy featured the same elevator traffic density.…”
Section: Main Contributionsmentioning
confidence: 66%
See 3 more Smart Citations
“…In the comparative study, various sets of representative buildings (i.e., Sets 1, 2, and 3 in Table 2) were selected, and the PTE numbers under the MCE-level earthquake were correspondingly quantified. It can be found that the mean standard deviation of three sets reaches 12.8 when the method proposed in Gu et al (2023) is adopted while that decreases to 4.0 when the population heatmap is utilized to quantify the popularities of buildings in this study, demonstrating that Gu et al (2023) is significantly sensitive to the selection of representative buildings while the population heatmap-powered method in this study is robust. In Gu et al (2023), it was assumed that buildings with the same occupancy featured the same elevator traffic density.…”
Section: Main Contributionsmentioning
confidence: 66%
“…It can be found that the mean standard deviation of three sets reaches 12.8 when the method proposed in Gu et al (2023) is adopted while that decreases to 4.0 when the population heatmap is utilized to quantify the popularities of buildings in this study, demonstrating that Gu et al (2023) is significantly sensitive to the selection of representative buildings while the population heatmap-powered method in this study is robust. In Gu et al (2023), it was assumed that buildings with the same occupancy featured the same elevator traffic density. This assumption ignores the significant variations between the population densities within different areas.…”
Section: Main Contributionsmentioning
confidence: 66%
See 2 more Smart Citations
“…The most recently published articles from the year 2023 presented five studies related to engineering and transportation [39][40][41][42][43]. Shi and Zhu [39] proposed a dual-phase control strategy for cargo transportation using a partial space elevator, which effectively balances multiple control objectives and achieves a stable equilibrium state.…”
Section: Related Literaturementioning
confidence: 99%